The knowledge and skills gap of medical practitioners delivering district hospital services in the Western Cape, South Africa - M.R. de Villiers; P.J.T. de Villiers (South African Family Practice)
Introduction: District (community) hospitals play an important role in the delivery of health services at community level, especially in rural areas. These hospitals provide comprehensive level-one health services to their communities, and serve as a resource for the whole health district. Most district hospitals are situated in rural areas, with medical services in these hospitals being rendered by generalist medical practitioners. The education and training of generalist practitioners for rural practice needs specific attention. Firstly, the unique nature of rural practice makes it necessary for doctors to undergo relevant and focused instruction. Rural family practice requires that doctors have the knowledge and skills to practise in settings where high technology and specialist resources are not available, while at the same time requiring that they be able to perform a wide range of advanced functions and procedures. Secondly, it is argued that appropriate education and training for rural practice can positively influence the recruitment and retention of medical practitioners in rural areas.5 The teaching of the knowledge and skills required for rural practice should take place in an appropriate setting that promotes interest in rural practice and familiarises the student with its particular challenges. There is a paucity of data in South Africa on medical practitioners staffing district hospitals, especially in terms of their knowledge and skills levels. Such information is critical if rural hospitals are to deliver equitable and quality health services, and also for guiding appropriate undergraduate, postgraduate and continuing professional education for rural practice. With this as background, health service managers in the Western Cape requested a skills audit of medical officers in district hospitals to identify a possible gap in competencies that may impact on service delivery. The aim of this study was thus to identify the knowledge and skills of medical practitioners delivering these services in the Western Cape and to compare them with service needs in order to make recommendations for education and training. This article reports on the results of the knowledge and skills gap analysis, while the results of the district hospital performance data and in-depth interviews are reported elsewhere.